Predictors Of Colon Cancer in Patients Referred to a Gastroenterologist for Iron Deficiency - Mark R., Borgaonkar; Kanwar, Wadhwa; Wendy, Winsor; Branko, Simeunovic; John M., Fardy (Journal of Digestive Disorders And Diagnosis, 2016)
Background: Iron deficiency is a common reason for referral to a gastroenterologist. Objective: To identify predictors of colorectal cancer in patients referred to a gastroenterologist for iron deficiency. Methods: This was a retrospective review of consecutive patients referred to one of two gastroenterologists for assessment of iron deficiency. The office files and electronic health records were reviewed for all patients. Clinical data, such as hemoglobin level, and clinical symptoms were recorded. The final diagnosis was that of the attending gastroenterologist. Variables associated with a diagnosis of colorectal cancer by univariate analysis were entered into a multivariate logistic regression model to identify variables independently associated with the diagnosis of colorectal cancer.  Results: Two hundred and seventy eight patients were included in this study. One hundred and fifty-eight (56.8%) were female. Mean age was 60.7 years (± 16.7 years). The most common causes of iron deficiency were: menorrhagia 16.2%, colorectal cancer 14%, use of aspirin or non-steroidal agents 11.2% and regular blood donation 7.2%. In 11.5% of patients, no cause was found. In univariate analysis, lower hemoglobin, greater age, shorter duration of iron deficiency, weight loss, symptoms from anemia and NSAID use were associated with colorectal cancer. In multivariate analysis, only older age (OR=1.06; 95% CI 1.04-1.09) and symptoms from anemia (OR=2.19; 95% CI 1.20-4.0) were independently associated with colorectal cancer. Conclusions: Colorectal cancer was found in 14% of patients referred to a gastroenterologist because of iron deficiency. Older age, and symptomatic anemia may help predict a diagnosis of colorectal cancer.
Keywords: Iron deficiency; Colorectal cancer; Gastrointestinal bleeding; Gastroscopy; Colonoscopy.